Carbon nanofiber yarns fabricated from co-electrospun nanofibers. (5th April 2016) - Zhou, Yuman; He, Jianxin; Wang, Hongbo; Qi, Kun; Ding, Bin; Cui, Shizhong
Abstract: Three different nanofiber yarns with various structures are first fabricated using a custom-made, coaxial, conjugate, electrospinning set-up. These yarns are then subjected to thermal stabilization and carbonization to obtain polyacrylonitrile-based carbon nanofiber yarns (PAN-based CNY), PAN/poly(methyl methacrylate)-based carbon nanofiber yarns (PAN/PMMA-based CNY), and C/Cu composite nanofiber yarns. The structures of the three CNYs are characterized using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectroscopy. The electrical conductivity of the samples is measured using a four-point probe method. In the case of the PAN-based CNY, the fibers strongly adhere to each other and eventually fracture, making the individual fibers no longer distinguishable from each other. On the other hand, the PAN/PMMA-based CNY and C/Cu composite nanofiber yarns are composed of independent fibers that are well oriented. Moreover, for the C/Cu composite nanofiber yarn, a nanowire composed of Cu nanoparticles is observed along the central axis of these fibers. In addition, Cu nanoparticles uniformly adhere to the surfaces of these fibers. Compared to the PAN-based CNY, the electrical conductivity of the C/Cu composite nanofiber yarns is significantly higher. Graphical abstract: Highlights: Obtained carbon nanofiber yarns are composed of independent nanofibers. C/Cu composite nanofiber yarn has a nanowire in the central axis of the fiber. The C/Cu composite nanofiber yarn exhibits an enhanced electrical conductivity. The method of fabricating CNYs is befit to prepare other polymer nanofiber yarn.